(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This essay is the account of a commented translation of Renaissance intellectual Niccolò Machiavelli’s comedy La Mandragola, adapted to Salvador da Bahia’s contemporary context. First and foremost, the translation process and its subsequent analysis allowed to highlight the importance of a careful study concerning Renaissance sexual vocabulary, in order to recreate in the text of arrival the double entendres found in the text of departure; such a study was feasible thanks to Valter Boggione’s (2016) research, which also points out political and social issues present in the play. Secondly, with the aid of Hannah Pitkin’s studies (2013), it was possible to underline some gender issues in Machiavelli’s play, in primis regarding the role of women. Practical translation challenges, amongst which the characters’ language, the hybrid features of a text that contains prose and poetry, and the historical and geographical distance between source-text culture and target-text culture, were highlighted and addressed via the technical translation procedures – particularly the concept of adaptation – systematized by Heloísa Gonçalves Barbosa (2004). Finally, the authors introduced the concept of “dramaturgical transplant”, a transfer process which takes place in the culture of arrival, at the same time revitalizing the culture of departure. Further than causing the text displacement, such a process displaces the very translator.